Anmeldelser - Erler, Annette (Danish Yearbook of Musicology, 2005)
Review of: Poul Rovsing Olsen: Music in Bahrain. Traditional Music of the Arabian Gulf, ed. Scheherazade Hassan, Tourif Kerbage, and Flemming Højlund Jysk Arkæologisk Selskabs Skrifter, 42; published by the Jutland Archaological Society in association with the Moesgaard Museum and the Ministry of Information, Kingdom of Bahrain; Århus: Aarhus University Press, 2002